Skepticism in early modern English literature the problems and pleasures of doubt - Sherman, Anita Gilman 1957- (Cambridge University Press, 2021)
This ambitious account of skepticism's effects on major authors of England's Golden Age shows how key philosophical problems inspired literary innovations in poetry and prose. When figures like Spenser, Shakespeare, Donne, Herbert of Cherbury, Cavendish, Marvell and Milton question theories of language, degrees of knowledge and belief, and dwell on the uncertainties of perception, they forever change English literature, ushering it into a secular mode. While tracing a narrative arc from medieval nominalism to late seventeenth-century taste, the book explores the aesthetic pleasures and political quandaries induced by skeptical doubt. It also incorporates modern philosophical views of skepticism: those of Stanley Cavell, Ludwig Wittgenstein, Roland Barthes, and Hans Blumenberg, among others. The book thus contributes to interdisciplinary studies of philosophy and literature as well as to current debates about skepticism as a secularizing force, fostering civil liberties and religious freedoms
Title from publisher's bibliographic system (viewed on 27 Apr 2021)
Introduction : secularizing skepticism? -- Visionary interrupted : Spenser's skeptical artwork -- Fantasies of private language : Shakespeare's "The Phoenix and turtle" and Donne's "The Ecstasy" -- Conformity/neutrality in Lord Herbert of Cherbury -- The skeptical fancies of Margaret Cavendish : reoccupation -- The enchantments of Andrew Marvell : skepticism and taste -- Afterword : experience in crisis - Milton's Samson Agonistes
Keywords: Geschichte 1500-1600; English literature / Early modern, 1500-1700 / History and criticism; Literature / Philosophy; Skepticism in literature; Literatur; Englisch; Skeptizismus